A Computational Investigation of Sources of Variability in Sentence Comprehension Difficulty in Aphasia. (22nd January 2018) - Mätzig, Paul; Vasishth, Shravan; Engelmann, Felix; Caplan, David; Burchert, Frank
Abstract: We present a computational evaluation of three hypotheses about sources of deficit in sentence comprehension in aphasia: slowed processing, intermittent deficiency, and resource reduction. The ACT‐R based Lewis and Vasishth (2005) model is used to implement these three proposals. Slowed processing is implemented as slowed execution time of parse steps; intermittent deficiency as increased random noise in activation of elements in memory; and resource reduction as reduced spreading activation. As data, we considered subject vs. object relative sentences, presented in a self‐paced listening modality to 56 individuals with aphasia (IWA) and 46 matched controls. The participants heard the sentences and carried out a picture verification task to decide on an interpretation of the sentence. These response accuracies are used to identify the best parameters (for each participant) that correspond to the three hypotheses mentioned above. We show that controls have more tightly clustered (less variable) parameter values than IWA; specifically, compared to controls, among IWA there are more individuals with slow parsing times, high noise, and low spreading activation. We find that (a) individual IWA show differential amounts of deficit along the three dimensions of slowed processing, intermittent deficiency, and resource reduction, (b) overall, there is evidence for all three sources of deficit playing a role, and (c) IWA have a more variable range of parameter values than controls. An important implication is that it may be meaningless to talk about sources of deficit with respect to an abstract verage IWA; the focus should be on the individual's differential degrees of deficit along different dimensions, and on understanding the causes of variability in deficit between participants. Abstract : A paper by Mätzig, Vasishth, Englemann, Caplan, and Burchert used an ACT‐R model based on previous work to evaluate three hypotheses about the observed lower comprehension of sentences by people with aphasia. They demonstrated tighter clustering of model parameters that matched control subjects' behavior compared to those matching the behavior of individuals with aphasia. This demonstrated that differences between the two groups could be explained by different model parameters.